Verification of crossmedia content for interactive digital television - Lisboa, Rafaela Ponte; Furtado, Maria Elizabeth; Borges Neto, Hermínio (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Since the standard interactive Digital Television (DTV) has been defined, there is the expectation of creation of universal network of Distance Education. But there are limitations concerning the techniques and profile of the Brazilian, however, one sees an improvement of the technology for use in educational settings and across many sectors. So this paper proposes recommendations for the production of such content, grouped into the categories of usability, communication and technology that were enriched from experiences with students of the public school system. The contribution of this research is a checklist to support in verification of production of content.